42-47g / m < 2 > ultra-low basis weight corrugating medium paper and production process thereof
By introducing a combination of kaolin and modified starch into the production of ultra-low basis weight corrugated core paper, a reinforced fiber-filler network structure is formed, solving the problems of insufficient paper strength and uneven production, and realizing the production of high-strength, low-cost corrugated core paper.
Patent Information
- Application Number
- CN202411343255.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-07
AI Technical Summary
Existing ultra-low basis weight corrugated core paper production suffers from problems such as weak inter-fiber bonding, insufficient paper strength, uneven production process, and high cost.
A modified reinforcing agent was prepared by combining kaolin, phthalimide, modified starch, polyethylene glycol and nanocellulose, and by processing methods such as ball milling and microwave radiation. The agent was then mixed with pulp, sizing agent was added, and the pulping and drying processes were controlled to form a reinforced fiber-filler network structure.
It significantly improves the structural strength and stability of corrugated core paper, reduces production basis weight, enhances the economic efficiency and environmental friendliness of the material, strengthens tensile strength and bursting strength, and reduces the risk of breakage.
Smart Images

Figure BDA0005060292970000051 
Figure BDA0005060292970000091 
Figure BDA0005060292970000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of packaging paperboard and relates to a 42-47g / m 2 Ultra-low weight corrugated core paper and its production process. Background Art
[0002] With the increasing global environmental awareness and the popularization of the concept of sustainable development, the paper products industry is facing huge challenges and opportunities, especially in the field of packaging materials. How to produce environmentally friendly, economical and efficient paper products has become the focus of the industry. As an important material in the packaging industry, the performance of corrugated core paper directly affects the protection effect and cost-effectiveness of packaging products.
[0003] In recent years, with the advancement of technology and changes in market demand, ultra-low-weight corrugated paper has gradually gained favor in the market due to its advantages of light weight, environmental protection and cost savings. However, there are many technical difficulties in the production process of ultra-low-weight corrugated paper. First, the fiber bonding force of low-weight paper is weak, which easily leads to insufficient paper strength and difficulty in meeting packaging requirements; secondly, how to effectively control the uniformity and stability of paper during the production process to avoid defects such as holes and cracks is also a major challenge. In addition, how to reduce production costs and improve production efficiency while ensuring paper performance is a key issue that needs to be urgently solved in the current packaging materials field. Summary of the invention
[0004] The object of the present invention is to provide a 42-47g / m 2 Ultra-low weight corrugated core paper and its production process have the characteristics of low weight, high hardness and damage resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A 42-47g / m 2 Ultra-low quantitative corrugated core paper, the formula of the corrugated core paper is as follows: by weight percentage, 80-90% of pulp slurry, 5-15% of modifying and reinforcing agent, 3-5% of sizing agent,
[0007] Wherein, the preparation method of the modified reinforcing agent is as follows:
[0008] S1-1: kaolin was placed in a ball mill for ball milling at a speed of 350 r / min for 30 min, and the milled kaolin was mixed with deionized water at a mass ratio of 1:4 to obtain a suspension A;
[0009] S1-2: Phthalic anhydride and urea were mixed and ball-milled in a ball mill at a speed of 300 r / min for 30 min. The mixture obtained by ball milling was mixed with a mixed solution of deionized water and ethanol at a mass ratio of 1:1, wherein the volume ratio of deionized water to ethanol was 2:1. The mixture was heated at 150° C. for 3 h, and washed and dried with deionized water to obtain powder B.
[0010] S1-3: Powder B was added to suspension A, and the mixture was stirred at 90°C and 2 MPa for 1.5 h to obtain a mixed solution C;
[0011] S1-4: corn starch and deionized water were mixed in a mass ratio of 2:3, stirred at a speed of 550 r / min for 10 min, 3 wt% β-amylase was added, and microwave radiation was used for heating at a temperature of 90° C. for 1 h, the temperature was increased to 110° C., the air pressure was increased to 3 MPa, and the heating time was 2 h to obtain a modified starch solution;
[0012] S1-5: adding the modified starch solution to the mixed solution C, wherein the volume ratio of the modified starch solution to the mixed solution C is 2:1, ultrasonicating for 40 minutes, adding 5wt% polyethylene glycol, stirring at 60°C for 1 hour, adding 5wt% nanocellulose solution, and continuing to stir at 60°C for 1 hour to obtain the modified enhancer.
[0013] Furthermore, the paper pulp slurry is one or more of wood pulp, bamboo pulp and straw pulp.
[0014] Furthermore, the sizing agent is a mixture of AKD emulsion and styrene-acrylic emulsion, wherein the volume ratio of AKD emulsion to styrene-acrylic emulsion is 2:1.
[0015] Furthermore, in the S1-2, phthalic anhydride and urea are mixed in a mass ratio of 1:1.
[0016] Furthermore, the solid-liquid mass ratio of the powder B and the suspension A in S1-3 is 1:9.
[0017] A production process for ultra-low basis weight corrugated medium paper, the production process specifically comprising the following steps:
[0018] S6-1: Filter and screen the pulp slurry according to the formula ratio to remove impurities, and then place it in a disc refiner for beating. The beating time is 50 minutes and the beating temperature is 45° C. to obtain a slurry;
[0019] S6-2: The modifier and the sizing agent are mixed and added to the slurry, and stirred in a water bath at 60°C for 1 hour at a stirring speed of 100 r / min. After stirring, constant temperature oscillation is performed for 2 hours to obtain a mixture;
[0020] S6-3: The mixed material is molded and dehydrated, and then squeezed and dehydrated. After dehydration, it is placed in a constant temperature drying oven at 100° C. for 12 hours to obtain the corrugated core paper.
[0021] Furthermore, the constant temperature oscillation parameters in S6-2 are set to a temperature of 40°C and a rotation speed of 150 r / min.
[0022] Furthermore, in S6-3, the molding dehydration is performed to a dryness of 20-30%, and the pressing dehydration is performed to a dryness of 50-60%.
[0023] As a high-quality filler, kaolin particles can penetrate and fill the tiny gaps between fibers, thereby effectively alleviating the problem of insufficient inter-fiber bonding and significantly improving the overall structural strength of corrugated core paper. In order to further enhance the performance and stability of kaolin, phthalimide, the reaction product of phthalic anhydride and urea under high temperature conditions, was introduced. This compound can be adsorbed on the surface or interlayer of kaolin through van der Waals forces and hydrogen bonds, which not only promotes the uniform dispersion of kaolin particles in the fiber matrix, but also significantly improves its stability. In addition, the amino groups in the phthalimide molecules are highly reactive. These amino groups may react chemically with the abundant hydroxyl groups on the surface of kaolin to form stable chemical bonds, further enhancing the bonding strength between kaolin and fibers. At the same time, the amino groups can also effectively interact with the hydroxyl groups on the surface of cellulose fibers to construct a more solid fiber-filler-fiber three-dimensional network structure, which not only optimizes the mechanical properties of corrugated core paper, but also helps to achieve lower production quantities and improve the economy and environmental friendliness of the material.
[0024] Corn starch is a natural adhesive and thickener. After being treated with β-amylase, the α-1,4-glycosidic bonds in the starch molecules are hydrolyzed, and β-amylase moderately shortens the starch molecular chain to form a modified starch with higher viscosity and better permeability. This modified starch can more effectively penetrate between paper fibers, forming a stronger bonding force, thereby improving the mechanical properties of the tensile strength and bursting strength of the corrugated core paper.
[0025] The added polyethylene glycol has good lubricity, which can reduce the friction resistance between the fiber and the filler, making them easier to disperse and mix in the pulp; polyethylene glycol can increase the flexibility and plasticity of the corrugated core paper, so that the corrugated core paper can better disperse stress when subjected to external force and reduce the possibility of rupture; in addition, polyethylene glycol can also stabilize the starch and kaolin components in the modified reinforcing agent to prevent them from stratification or precipitation during storage and use. The addition of nanocellulose can further improve the dispersion stability of fillers and fibers. Nanocellulose particles are small and have high surface energy. They can be effectively dispersed in the filler and improve the uniformity of the filler in the fiber matrix; nanocellulose forms a fine lubricating layer between fibers, reduces the friction between fibers, is beneficial to the arrangement of fibers and the molding of paper, and improves the overall structural strength of paper; in addition, due to its high specific surface area and excellent mechanical properties, nanocellulose can serve as a bridge between fibers, enhance the bonding force of the fiber network, and thus improve the overall structural strength of paper.
[0026] The introduction of styrene acrylic emulsion and AKD emulsion as sizing agents can further improve the bonding strength between fibers, thereby improving the physical properties of corrugated core paper; in addition, both styrene acrylic emulsion and AKD emulsion have good water resistance. Styrene acrylic emulsion prevents moisture penetration by penetrating paper fibers to form a network structure, while AKD emulsion can form a hydrophobic layer on the fiber surface. The combination of the two can form a more effective water-resistant barrier, significantly improving the water resistance and moisture resistance of corrugated core paper.
[0027] Beneficial effects of the present invention:
[0028] (1) By introducing phthalimide into kaolin, the structural strength and stability of corrugated core paper are significantly improved. The active amino groups of phthalimide react chemically with the hydroxyl groups on the surface of kaolin and paper fibers to build a stronger fiber-filler-fiber network structure, which not only optimizes the mechanical properties of corrugated core paper, but also achieves a lower production quantity, improving the economic and environmental friendliness of the material.
[0029] (2) The use of β-amylase to treat corn starch produced a high-viscosity, highly permeable modified starch, which was used as an adhesive to significantly improve the tensile strength and burst strength of the corrugated core paper. The addition of polyethylene glycol and nanocellulose further improved the dispersion and mixing effect of the fiber and filler in the pulp, improved the strength of the corrugated core paper, and enhanced the stress dispersion ability of the corrugated core paper when it was stressed, reducing the risk of rupture. DETAILED DESCRIPTION
[0030] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0031]
[0032] Example 1
[0033] Formula 1, by weight percentage, includes 85% of softwood pulp, 10% of a modifying and reinforcing agent, and 5% of a sizing agent, wherein the sizing agent is a mixture of AKD emulsion and styrene-acrylic emulsion in a volume ratio of 2:1.
[0034] Wherein, the preparation method of the modified reinforcing agent is as follows:
[0035] S1-1: kaolin was placed in a ball mill for ball milling at a speed of 350 r / min for 30 min, and the milled kaolin was mixed with deionized water at a mass ratio of 1:4 to obtain a suspension A;
[0036] S1-2: Phthalic anhydride and urea were mixed in a mass ratio of 1:1, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 30 min. The mixture obtained by ball milling was mixed with a mixed solution of deionized water and ethanol in a mass ratio of 1:1, wherein the volume ratio of deionized water to ethanol was 2:1, and the mixture was heated at 150°C for 3 h. The mixture was washed with deionized water and dried to obtain powder B.
[0037] S1-3: Powder B is added to suspension A, wherein the solid-liquid mass ratio of powder B to suspension A is 1:9, and stirred at a temperature of 90°C and a pressure of 2MPa for 1.5h to obtain a mixed solution C;
[0038] S1-4: corn starch and deionized water were mixed in a mass ratio of 2:3, stirred at a speed of 550 r / min for 10 min, 3 wt% β-amylase was added, and microwave radiation was used for heating at a temperature of 90° C. for 1 h, the temperature was increased to 110° C., the air pressure was increased to 3 MPa, and the heating time was 2 h to obtain a modified starch solution;
[0039] S1-5: adding the modified starch solution to the mixed solution C, wherein the volume ratio of the modified starch solution to the mixed solution C is 2:1, ultrasonicating for 40 minutes, adding 5wt% polyethylene glycol, stirring at 60°C for 1 hour, adding 5wt% nanocellulose solution, and continuing to stir at 60°C for 1 hour to obtain the modified enhancer.
[0040] The production process of ultra-low quantitative corrugated core paper specifically includes the following steps:
[0041] S7-1: According to formula 1, the wood pulp is filtered and screened to remove impurities, and then placed in a disc refiner for beating. The beating time is 50 minutes and the beating temperature is 45° C. to obtain a slurry, wherein the moisture content of the slurry is 75%;
[0042] S7-2: The modifier and the sizing agent are mixed and added to the slurry, and stirred in a water bath at 60°C for 1 hour at a stirring speed of 100 r / min. After stirring, constant temperature oscillation is performed for 2 hours, and the constant temperature oscillation parameters are set to a temperature of 40°C and a speed of 150 r / min to obtain a mixture;
[0043] S7-3: The mixed material is molded and dehydrated to a dryness of 25%, and then pressed and dehydrated to a dryness of 55%. After dehydration, the mixed material is placed in a constant temperature drying oven at 100° C. for 12 hours to obtain the corrugated core paper.
[0044] Example 2
[0045] Formula 2, by weight percentage, softwood pulp 90%, modifier 5%, sizing agent
[0046] 5%, the sizing agent is a mixture of AKD emulsion and styrene acrylic emulsion in a volume ratio of 2:1.
[0047] Wherein, the preparation method of the modified reinforcing agent is as follows:
[0048] S1-1: kaolin was placed in a ball mill for ball milling at a speed of 350 r / min for 30 min, and the milled kaolin was mixed with deionized water at a mass ratio of 1:4 to obtain a suspension A;
[0049] S1-2: Phthalic anhydride and urea were mixed in a mass ratio of 1:1, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 30 min. The mixture obtained by ball milling was mixed with a mixed solution of deionized water and ethanol in a mass ratio of 1:1, wherein the volume ratio of deionized water to ethanol was 2:1, and the mixture was heated at 150°C for 3 h. The mixture was washed with deionized water and dried to obtain powder B.
[0050] S1-3: Powder B is added to suspension A, wherein the solid-liquid mass ratio of powder B to suspension A is 1:9, and stirred at a temperature of 90°C and a pressure of 2MPa for 1.5h to obtain a mixed solution C;
[0051] S1-4: corn starch and deionized water were mixed in a mass ratio of 2:3, stirred at a speed of 550 r / min for 10 min, 3 wt% β-amylase was added, and microwave radiation was used for heating at a temperature of 90° C. for 1 h, the temperature was increased to 110° C., the air pressure was increased to 3 MPa, and the heating time was 2 h to obtain a modified starch solution;
[0052] S1-5: adding the modified starch solution to the mixed solution C, wherein the volume ratio of the modified starch solution to the mixed solution C is 2:1, ultrasonicating for 40 minutes, adding 5wt% polyethylene glycol, stirring at 60°C for 1 hour, adding 5wt% nanocellulose solution, and continuing to stir at 60°C for 1 hour to obtain the modified enhancer.
[0053] The production process of ultra-low quantitative corrugated core paper specifically includes the following steps:
[0054] S7-1: According to recipe 2, the wood pulp is filtered and screened to remove impurities, and then placed in a disc refiner for beating. The beating time is 50 minutes and the beating temperature is 45° C. to obtain a slurry, wherein the moisture content of the slurry is 75%;
[0055] S7-2: The modifier and the sizing agent are mixed and added to the slurry, and stirred in a water bath at 60°C for 1 hour at a stirring speed of 100 r / min. After stirring, constant temperature oscillation is performed for 2 hours, and the constant temperature oscillation parameters are set to a temperature of 40°C and a speed of 150 r / min to obtain a mixture;
[0056] S7-3: The mixed material is molded and dehydrated to a dryness of 25%, and then pressed and dehydrated to a dryness of 55%. After dehydration, the mixed material is placed in a constant temperature drying oven at 100° C. for 12 hours to obtain the corrugated core paper.
[0057] Example 3
[0058] Formula 3, by weight percentage, softwood pulp 80%, modifier 15%, sizing agent
[0059] 5%, the sizing agent is a mixture of AKD emulsion and styrene acrylic emulsion in a volume ratio of 2:1.
[0060] Wherein, the preparation method of the modified reinforcing agent is as follows:
[0061] S1-1: kaolin was placed in a ball mill for ball milling at a speed of 350 r / min for 30 min, and the milled kaolin was mixed with deionized water at a mass ratio of 1:4 to obtain a suspension A;
[0062] S1-2: Phthalic anhydride and urea were mixed in a mass ratio of 1:1, and the mixture was ball-milled in a ball mill at a speed of 300 r / min for 30 min. The mixture obtained by ball milling was mixed with a mixed solution of deionized water and ethanol in a mass ratio of 1:1, wherein the volume ratio of deionized water to ethanol was 2:1, and the mixture was heated at 150°C for 3 h. The mixture was washed with deionized water and dried to obtain powder B.
[0063] S1-3: Powder B is added to suspension A, wherein the solid-liquid mass ratio of powder B to suspension A is 1:9, and stirred at a temperature of 90°C and a pressure of 2MPa for 1.5h to obtain a mixed solution C;
[0064] S1-4: corn starch and deionized water were mixed in a mass ratio of 2:3, stirred at a speed of 550 r / min for 10 min, 3 wt% β-amylase was added, and microwave radiation was used for heating at a temperature of 90° C. for 1 h, the temperature was increased to 110° C., the air pressure was increased to 3 MPa, and the heating time was 2 h to obtain a modified starch solution;
[0065] S1-5: adding the modified starch solution to the mixed solution C, wherein the volume ratio of the modified starch solution to the mixed solution C is 2:1, ultrasonicating for 40 minutes, adding 5wt% polyethylene glycol, stirring at 60°C for 1 hour, adding 5wt% nanocellulose solution, and continuing to stir at 60°C for 1 hour to obtain the modified enhancer.
[0066] The production process of ultra-low quantitative corrugated core paper specifically includes the following steps:
[0067] S7-1: According to recipe 3, the wood pulp was filtered and screened to remove impurities, and then placed in a disc refiner for beating. The beating time was 50 minutes and the beating temperature was 45° C. to obtain a slurry, wherein the moisture content of the slurry was 75%;
[0068] S7-2: The modifier and the sizing agent are mixed and added to the slurry, and stirred in a water bath at 60°C for 1 hour at a stirring speed of 100 r / min. After stirring, constant temperature oscillation is performed for 2 hours, and the constant temperature oscillation parameters are set to a temperature of 40°C and a speed of 150 r / min to obtain a mixture;
[0069] S7-3: The mixed material is molded and dehydrated to a dryness of 25%, and then pressed and dehydrated to a dryness of 55%. After dehydration, the mixed material is placed in a constant temperature drying oven at 100° C. for 12 hours to obtain the corrugated core paper.
[0070] Comparative Example 1
[0071] Phthalic anhydride and urea were not added to the modified enhancer, and the remaining steps were consistent with those in Example 1.
[0072] Comparative Example 2
[0073] No β-amylase was added to the modified enhancer, and the remaining steps were consistent with those in Example 1.
[0074] Comparative Example 3
[0075] No polyethylene glycol was added to the modified enhancer, and the remaining steps were consistent with those in Example 1.
[0076] Comparative Example 4
[0077] No nanocellulose solution was added to the modified reinforcing agent, and the remaining steps were consistent with those in Example 1.
[0078] The tensile strength of the embodiments and comparative examples was tested according to the method of GB / T 12914-2018 "Determination of tensile strength of paper and paperboard-Constant rate tensile method";
[0079] The bursting resistance index of the embodiment and the comparative example was tested according to the method of GB / T 454-2020 "Determination of bursting resistance of paper";
[0080] The quantitative test of the examples and comparative examples was carried out according to the method of GB T 451.2-2002 “Determination of the Quantitative Weight of Paper and Paperboard”.
[0081] The experimental results are summarized in the following table:
[0082]
[0083]
[0084] It can be seen from the data of the embodiments and comparative examples that the introduction of phthalimide into kaolin significantly improves the structural strength of corrugated core paper and reduces the basis weight; the tensile strength and bursting strength of corrugated core paper are improved after corn starch is treated with β-amylase; the addition of polyethylene glycol and nanocellulose reduces the risk of rupture, and nanocellulose also improves the strength of corrugated core paper.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A 42-47g / m 2 Ultra-low weight corrugated core paper, characterized in that: The formula of the corrugated core paper is as follows: by weight percentage, 80-90% of pulp slurry, 5-15% of modifying and reinforcing agent, and 3-5% of sizing agent. Wherein, the preparation method of the modified reinforcing agent is as follows: S1-1: kaolin was placed in a ball mill for ball milling at a speed of 350 r / min for 30 min, and the ball milled kaolin was mixed with deionized water at a mass ratio of 1:4 to obtain a suspension A; S1-2: Phthalic anhydride and urea were mixed and ball-milled in a ball mill at a speed of 300 r / min for 30 min. The mixture obtained by ball milling was mixed with a mixed solution of deionized water and ethanol at a mass ratio of 1:1, wherein the volume ratio of deionized water to ethanol was 2:
1. The mixture was heated at 150° C. for 3 h, and washed and dried with deionized water to obtain powder B. S1-3: Powder B was added to suspension A, and the mixture was stirred at 90°C and 2 MPa for 1.5 h to obtain a mixed solution C; S1-4: corn starch and deionized water were mixed in a mass ratio of 2:3, stirred at a speed of 550 r / min for 10 min, 3 wt% β-amylase was added, and microwave radiation was used for heating at a temperature of 90° C. for 1 h, the temperature was increased to 110° C., the air pressure was increased to 3 MPa, and the heating time was 2 h to obtain a modified starch solution; S1-5: adding the modified starch solution to the mixed solution C, wherein the volume ratio of the modified starch solution to the mixed solution C is 2:1, ultrasonicating for 40 minutes, adding 5wt% polyethylene glycol, stirring at 60°C for 1 hour, adding 5wt% nanocellulose solution, and continuing to stir at 60°C for 1 hour to obtain the modified enhancer.
2. A 42-47 g / m2 according to claim 1 2 Ultra-low weight corrugated core paper, characterized in that: The paper pulp slurry is one or more of wood pulp, bamboo pulp and straw pulp.
3. A 42-47g / m2 according to claim 1 2 Ultra-low weight corrugated core paper, characterized in that: The sizing agent is a mixture of AKD emulsion and styrene-acrylic emulsion, wherein the volume ratio of AKD emulsion to styrene-acrylic emulsion is 2:
1.
4. A 42-47g / m 2 Ultra-low weight corrugated core paper, characterized in that: In the S1-2, phthalic anhydride and urea are mixed in a mass ratio of 1:
1.
5. A 42-47g / m2 according to claim 1 2 Ultra-low weight corrugated core paper, characterized in that: The solid-to-liquid mass ratio of powder B to suspension A in S1-3 is 1:
9.
6. A process for producing ultra-low basis weight corrugated medium paper according to any one of claims 1 to 5, characterized in that: The production process specifically comprises the following steps: S6-1: Filter and screen the pulp slurry according to the formula ratio to remove impurities, and then place it in a disc refiner for beating. The beating time is 50 minutes and the beating temperature is 45° C. to obtain a slurry; S6-2: The modifier and the sizing agent are mixed and added to the slurry, and stirred in a water bath at 60°C for 1 hour at a stirring speed of 100 r / min. After stirring, constant temperature oscillation is performed for 2 hours to obtain a mixture; S6-3: The mixed material is molded and dehydrated, and then squeezed and dehydrated. After dehydration, it is placed in a constant temperature drying oven at 100° C. for 12 hours to obtain the corrugated core paper.
7. The process for producing ultra-low basis weight corrugated medium paper according to claim 6, characterized in that: The constant temperature oscillation parameters in S6-2 are set to a temperature of 40°C and a rotation speed of 150 r / min.
8. The process for producing ultra-low basis weight corrugated medium paper according to claim 6, characterized in that: In the S6-3, the molding dehydration is performed to a dryness of 20-30%, and the pressing dehydration is performed to a dryness of 50-60%.
Citation Information
Patent Citations
Modified corrugated paper, and preparation method and application thereof
CN110158361A
High-strength corrugated core paper and production method thereof
CN111945474A
Low-basis-weight corrugated medium paper and production process thereof
CN116556097A
Cited By
Preparation method of papermaking sizing starch
CN119842840A